Experimental, analytical and numerical investigation on auto-ignition of thermally intermediate PMMA imposed to linear time-increasing heat flux. (25th May 2020) - Gong, Junhui; Zhang, Mingrui; Zhai, Chunjie; Yang, Lizhong; Zhou, Yang; Wang, Zhirong
Highlights: Auto-ignition of finite thick PMMA is studied under linear time-increasing heat flux. Analytical and numerical models are developed to validate the experimental data. Thermally inert assumption is not appropriate in predicting auto-ignition time. Thermal insulation should be considered for thermally intermediate ignition cases. Measured and modified ignition temperatures are 695 ± 14.5 K and 695 ± 30 K, respectively. Abstract: Auto-ignition of finite thick PMMA (polymethyl methacrylate) subjected to linear time-increasing heat flux ( HF ) is experimentally investigated utilizing a heating apparatus capable of freely controlling the variation of the exposure. Ignition times, surface and in-depth temperatures of samples were recorded. Theoretical analysis, using critical temperature, and numerical simulations considering pyrolysis and thermal insulation layer were implemented to estimate the corresponding measurements. Approximate correlations are obtained based on the analysis and they are related to the ones in thermally thick cases. Results show that the thermal insulation layer and the pyrolysis in solid have limited and significant effects on surface temperature, respectively. 1 mm PMMA cannot be treated as thermally thin due to the large temperature gradient in solid. Appreciable sample distortion and thickness regression observed in thin sample tests are responsible for the large uncertainty of ignition time and non-ignition phenomenon. Thinner sample and larger increasing rate of HF would lead to higher surface temperature and shorter ignition time. Two stages separated by pyrolysis temperature are identified before ignition. The measured critical temperature is 695 ± 14.5 K, and a more reasonable uncertainty range, ±30 K, is suggested by numerically fitting the measured ignition times.